Pengembangan Media Pembelajaran Ludo Untuk Materi Logaritma - Vilandina Alif Kamin; Della Safitri; Fitra Setya Dwi Utami; Leonard Leonard (Journal of Instructional Development Research, 2020)
This study aims as a tool in learning to be more interesting, happy to be active and interactive between the teacher and students. In this development, the development model used is referring to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model that is used to produce certain products and test the effectiveness of these products. The researcher concludes that the use of instructional media is very important in the teaching and learning process. Therefore, meaningful learning activities are needed so that students can master the concepts and properties of logarithms which are prerequisites for logarithmic functions. Ludo game is a type of game that is fun and entertaining to do, Ludo games can be played in groups that can increase interaction between students and their groups to support mutual cooperation and communicate well in order to finish the game. This research was developed to help students and teachers in learning mathematics using ludo media so that learning is more interesting.